2000
DOI: 10.1097/00007890-200006150-00042
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Does Not Promote Cellular or Humoral Activation Among Heart Transplant Recipients

Abstract: Despite the small number of patients in the study, influenza vaccination did not induce undesirable side effects, such as graft rejection or allo-sensitization. Generation of a positive anti-vaccine response was lower among the transplant recipients than healthy volunteers (41% vs. 80%). Clinical efficacy of the vaccine among the responders was not evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 4 publications
4
35
1
Order By: Relevance
“…Figure S1). In a single patient (1.6%) (10,26,(29)(30)(31)(32)(33). Furthermore, our data confirm and extend the results of the single study which analyzed postvaccinal HLA antibodies and showed that in heart transplant recipients no significant donor-specific allosensitization was induced by influenza vaccination (30).…”
Section: Anti-influenza Antibodiessupporting
confidence: 87%
See 1 more Smart Citation
“…Figure S1). In a single patient (1.6%) (10,26,(29)(30)(31)(32)(33). Furthermore, our data confirm and extend the results of the single study which analyzed postvaccinal HLA antibodies and showed that in heart transplant recipients no significant donor-specific allosensitization was induced by influenza vaccination (30).…”
Section: Anti-influenza Antibodiessupporting
confidence: 87%
“…In a single patient (1.6%) (10,26,(29)(30)(31)(32)(33). Furthermore, our data confirm and extend the results of the single study which analyzed postvaccinal HLA antibodies and showed that in heart transplant recipients no significant donor-specific allosensitization was induced by influenza vaccination (30). In our study, the use of a highly sensitive technique allowed us to identify a significant proportion of patients (22 (10,13,34,35 (12)(13)(14) as well as to other types of vaccine such as hepatitis B (37,38), presumably linked to immunosuppressive therapy (14)(15)(16)(17).…”
Section: Anti-influenza Antibodiesmentioning
confidence: 99%
“…Both bone marrow and solid organ transplant recipients exhibit increased morbidity from influenza infection (14,15). Annual vaccination of organ transplant recipients against influenza is recommended, safe, and does not result in allograft rejection (16). However, transplant recipients treated with conventional immunosuppression mount significantly impaired responses to influenza immunization (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Its safety and efficacy in liver transplant and other solid-organ recipients have been proven in several studies. 19,[21][22][23][24][25] Although our case suggests that GBS may occur in liver transplant recipients after influenza vaccination, the very low incidence of vaccine-associated GBS, the significantly increased complications from influenza virus infection in solid organ recipients, and the rise of influenza drug resistance make influenza vaccination the first-line strategy for influenza virus infection prevention in solid-organ recipients. 26,27 This fact is supported by the current guidelines for vaccination of solid-organ recipients.…”
Section: Discussionmentioning
confidence: 80%